2018
DOI: 10.5696/22156-9614-8.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Initial Inventory of Plastics Imports in Nigeria as a Basis for More Sustainable Management Policies

Abstract: Background.Plastic is a waste stream with recycling and recovery potential. However, the recycling rates for plastic in African countries are low. Furthermore, use and production of virgin plastics are increasing. Therefore, a high proportion of plastic waste is being disposed of in landfills and dumpsites. Plastic serves as fuel for open burning at landfills/dumpsites with associated releases and constitutes a large fraction of marine litter, making it a major and growing global pollution concern.Objectives.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Low-density polyethylene has been majorly imported into Nigeria over the last two decades and then used to produce a wide range of plastic products (grocery bags, cling wraps, sandwich bags, bubble wrap, fertilizer sacks, refuse bags and plastic bottles). However, these are often used once and discarded [5,11]. Additionally, polypropylene has also been used majorly in Nigeria's manufacturing industries.…”
Section: Plastic Waste In Nigeriamentioning
confidence: 99%
See 3 more Smart Citations
“…Low-density polyethylene has been majorly imported into Nigeria over the last two decades and then used to produce a wide range of plastic products (grocery bags, cling wraps, sandwich bags, bubble wrap, fertilizer sacks, refuse bags and plastic bottles). However, these are often used once and discarded [5,11]. Additionally, polypropylene has also been used majorly in Nigeria's manufacturing industries.…”
Section: Plastic Waste In Nigeriamentioning
confidence: 99%
“…Even though plastic is considered to have high recycling and recovery potential, the rate of recycling, which is reported to be less than 12% in Nigeria [5], does not match the fast pace at which plastics are being produced. For instance, the reported rate still falls short when compared to other neighboring regions like Cameroon, where it has been reported that the annual recycling rate of plastic waste is 20% [4].…”
Section: Plastic Waste In Nigeriamentioning
confidence: 99%
See 2 more Smart Citations
“…Plastics wastes are hardly recycled in Nigeria with less than 12% being recycled and about 80% of these wastes end up in landfills and dump sites [17]. Meanwhile landfills have been reported to contribute about 20% of Green House Gases (GHG) such as carbon dioxide (CO 2 ), methane (CH 4 ), sulphur and nitrogen gases, and fossil fuels [18].…”
Section: Impact Of Plastic Waste On Land Pollutionmentioning
confidence: 99%